Abundances of CNO elements in z ∼ 0.3–0.4 Lyman continuum leaking galaxies. Issue 1 (6th April 2023) - Izotov, Y I; Schaerer, D; Worseck, G; Berg, D; Chisholm, J; Ravindranath, S; Thuan, T X
ABSTRACT: We present observations with the Space Telescope Imaging Spectrograph onboard the Hubble Space Telescope ( HST ) of 11 Lyman continuum (LyC) leaking galaxies at redshifts, z, in the range 0.29–0.43, with oxygen abundances 12+log(O/H) = 7.64–8.16, stellar masses M ⋆  ∼ 10 7.8 –10 9.8  M⊙, and O32  = [O iii ] λ5007/[O ii ] λ3727 of ∼ 5–20 aiming to detect the C iii ] λ1908 emission line. We combine these observations with the optical Sloan Digital Sky Survey (SDSS) spectra for the determination of carbon, nitrogen, and oxygen abundances. Our sample was supplemented by 31 galaxies from the literature, for which carbon, nitrogen, and oxygen abundances can be derived from the HST and SDSS spectra. These additional galaxies, however, do not have LyC observations. We find that log(C/O) for the entire sample at 12+log(O/H) < 8.1 does not depend on metallicity, with a small dispersion of ∼0.13 dex around the average value of ∼−0.75 dex. On the other hand, the log(N/O) in galaxies at z  > 0.1, including LyC leakers, is systematically higher compared to the rest of the sample with lower metallicity. We find that log(C/O) slightly decreases with increasing M ⋆ from ∼ −0.65 at M ⋆  = 10 6  M⊙ to ∼ −0.80 at M ⋆  = 10 9 –10 10  M⊙, whereas log(N/O) is considerably enhanced at M ⋆  > 10 8  M⊙ . The origin of these trends remains basically unknown. A possible solution would be to assume that the upper mass limit of the stellar initial mass function in more massive galaxies is higher. This would result in a higher production of oxygen and a larger fraction of massive stars with stellar wind polluting the interstellar medium with nitrogen.